Personal Financial Planning - KOH, Benedict (Institutional Knowledge at Singapore Management University, 2011)
If you are like most people, you may desire to achieve many financial goals such as owning assets, saving money for emergency purposes, protecting yourself and your loved ones with insurance, and many more. Nonetheless, achieving these goals with limited resources can be challenging, especially given the complexity of modern financial markets. In this fourth and latest edition, Personal Financial Planning expands on the important skill of financial planning, covering more topics than before. This volume is designed to help you formulate financial goals and develop specific financial plans to achieve your goals. Topics covered in this volume include the benefits of personal financial planning, financial planning tools, managing credit, insurance planning, income tax planning, retirement planning, and personal financial risk management, among others. The authors are professionals with many years of experience in the field, and key terms and concepts are explained in a fuss-free manner with clear and relevant examples.